Concept of Calligraphy Learning at Pondok Pesantren Traditional Musthafawiyah Purbabaru, Mandailing Natal North Sumatra - Maulida Rahmi; Sayed Muhammad Ichsan (Jurnal Eduslamic, 2023)
Calligraphy is a well-known art in the Islamic world, so as Muslims, we must know what calligraphy. Calligraphy is also an art that has developed widely, especially in Islamic educational institutions. Calligraphy is also one of the arts that are in great demand, especially among those who has art and skills. Calligraphy is studied in various educational institutions but the calligraphy learning system between them has differences. The purpose of this research is to find out the calligraphy learning system in traditional boarding school. This research uses a literature study method and a type of qualitative method by conducting a field research approach. Data collection and analysis using interview techniques, researchers conducted interviews with several sources. The results showed that the calligraphy learning system in traditional boarding school is obligatory and some make it extracurricular, for those who require it, the learning system is held once a week, with the teacher system explaining in front of the class then the students do trials and practice.